The health system accountability impact of prison health committees in Zambia - Stephanie M. Topp; Anjali Sharma; Chisela Chileshe; George Magwende; German Henostroza; Clement N. Moonga (BMC, 2018)
Abstract Background From 2013, the Zambian Corrections Service (ZCS) worked with partners to strengthen prison health systems and services. One component of that work led to the establishment of facility-based Prison Health Committees (PrHCs) comprising of both inmates and officers. We present findings from a nested evaluation of the impact of eight PrHCs 18 months after programme initiation. Methods In-depth-interviews were conducted with 11 government ministry and Zambia Corrections Service officials and 6 facility managers. Sixteen focus group discussions were convened separately with PrHC members (21 females and 51 males) and non-members (23 females and 46 males) in 8 facilities. Memos were generated from participant observation in workshops and meetings preceding and after implementation. We sought evidence of PrHC impact, refined with reference to Joshi's three domains of impact for social accountability interventions - state (represented by facility-based prison officials), society (represented here by inmates), and state-society relations (represented by inmate-prison official relations). Further analysis considered how project outcomes influenced structural dimensions of power, ability and justice relating to accountability. Results Data pointed to a compelling series of short- and mid-term outcomes, with positive impact on access to, and provision of, health services across most facilities. Inmates (members and non-members) reported being empowered via a combination of improved health literacy and committee members' newly-given authority to seek official redress for complaints and concerns. Inmates and officers described committees as improving inmate-officer relations by providing a forum for information exchange and shared decision making. Contributing factors included more consistent inmate-officer communications through committee meetings, which in turn enhanced trust and co-production of solutions to health problems. Nonetheless, long-term sustainability of accountability impacts may be undermined by permanently skewed power relations, high rates of inmate (and thus committee member) turnover, variable commitment from some officers in-charge, and the anticipated need for more oversight and resources to maintain members' skills and morale. Conclusion Our study shows that PrHCs do have potential to facilitate improved social accountability in both state and societal domains and at their intersection, for an extremely vulnerable population. However, sustained and meaningful change will depend on a longer-term strategy that integrates structural reform and is delivered through meaningful cross-sectoral partnership.